Severe Asthma Patients Experience and Satisfaction with Virtual Clinics during COVID-19 Period - Khan, Mohammad Ayaz; Rajkumar, Rajendram; Hammadi, Mohammad; Al-Gamedi, Majed; Al-Harbi, Abdullah; Al-Jahdali, Hamdan (Avicenna Journal of Medicine, 2021)
Background Enforced social distancing (i.e., lockdowns) greatly facilitated control of coronavirus disease-19 (COVID-19). While access to hospitals was restricted, outpatient care continued remotely. The aim of this study was to determine the satisfaction of patients with severe asthma with telemedicine, and the impact of COVID-19 lockdown on severe asthma patients on biologics therapy.Methods A cross-sectional survey of patients with severe asthma scheduled to receive biologic therapy at our hospital during the lockdown. The survey had sections about demographic data, asthma history, subjective perception of change in asthma control with biologic agent, the effect of COVID-19 pandemic on access to maintenance therapy for asthma, asthma exacerbation management, and satisfaction with telephone follow-up.Results Fifty-four patients participated (response rate 93.1%; male 17; mean age 46.7 years). All had been on biologic therapy for over 3 months (mean 38.4 months ± standard deviation 26.5 months). Of the 45 patients living in Riyadh, 9 did not receive biologic therapy. Five of the nine patients living outside Riyadh did not receive biologic therapy. Alarmingly, 16 (29.6%) had insufficient medications, and 27 (50%) had difficulty obtaining medications. Fifty (92.6%) had telephone follow-up, 31 (57.4%) were satisfied with telemedicine.Conclusion Many patients were satisfied with telemedicine, so this could be used to deliver routine outpatient tertiary care postpandemic. However, logistics around supplying medications and biologics must be considered in plans preparing for the second wave of COVID-19.
Keywords: asthma; biological therapy; COVID-19; SARS-CoV-2; outpatient